PELAKSANAAN INSTRUKSI MEDIS VIA TELEPON OLEH PERAWAT DI RUANG RAWAT INAP RUMAH SAKIT ISLAM YARSIS SURAKARTA - , Megi akbar, drg. Suryono, S.H., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Medical instruction to the nurse must be in writing, but in the fact the nurse often accept and implement medical instruction verbally via telephone. The purpose of this research was to determine the occurrence of medical instructions doctors were given via telephone to the nurse, knowing kind of instructions doctors were given via telephone to the nurse, reviewing and analyzing the legal nurse liability as implementers of medical instruction via telephone in the ward Surakarta Islamic Hospital. The subjects were nurses who worked in the ward and the medical staff committee of Surakarta Islamic Hospital. Samples were determined using a Non-Random purposive sampling technique. The data was collected through interviews and study document. The results of this research are medical instruction via telephone occurs due to the limited number of the ward physician who has a duty to report the condition of patients in no more than 30 minutes to the Responsible Care Doctor (DPJP), because in 30 minutes the ward attending physician can not report the patient's condition to DPJP, consequently, nurse must report the patient condition to DPJP and DPJP finally gave instructions to the nurse. The instruction given consisted of two types, medical act and nursing act instructions. Instruction in the form of medical acts are provision of oral and injectable medications, inserting an IV drip, NGT, ETT, DC, O2 cannula over 3 liters, NRM, Nebulizer, and implementation of Torakosintesis, while instruction nursing actions are setting bed rest patients, delivering patient to X-rays, collaboration with physiotherapist, wound care, calculating fluid balance, doing compress, taking blood samples, vital sign observations, caring before and after surgery, doing of patient personal hygiene, consulting with nutrition installation, rinsing the hull, as well as, mobilizing and motivating patients. Nurses in the ward Surakarta Islamic Hospital are not alone responsible in case of undesirable events that happened to the patient due to the implementation of medical instruction via telephone that does. Responsibilities are also covered by the doctor and hospital.